Processo coletivo extrajudicial: a construção de consensos em conflitos coletivos como instrumento de controle de políticas públicas - Ludmila Costa Reis (2018)
The research indicates the insufficient normative treatment, by the Brazilian legal system, of consensual methods to solve conflicts involving public policies. The comparative analysis of foreign court orders that issued injunctions against the State demonstrates the need to deepen the study and practice of consensus methods of collective dispute resolution, which are necessary, even after filing a lawsuit, for achievement of the substantive right pleaded. Therefore, it is proposed a methodological extension of the object of study of the collective procedural law and, consequently, the development of the so-called extra-judicial collective process as an adequate method of controlling public policies through the construction of consensuses among the actors involved in conflicts of public interest.